Prediction of nonlinear evolution character of energetic-particle-driven instabilities. (17th March 2017) - Duarte, V.N.; Berk, H.L.; Gorelenkov, N.N.; Heidbrink, W.W.; Kramer, G.J.; Nazikian, R.; Pace, D.C.; Podestà, M.; Tobias, B.J.; Van Zeeland, M.A.
Abstract: A general criterion is proposed and found to successfully predict the emergence of chirping oscillations of unstable Alfvénic eigenmodes in tokamak plasma experiments. The model includes realistic eigenfunction structure, detailed phase-space dependences of the instability drive, stochastic scattering and the Coulomb drag. The stochastic scattering combines the effects of collisional pitch angle scattering and micro-turbulence spatial diffusion. The latter mechanism is essential to accurately identify the transition between the fixed-frequency mode behavior and rapid chirping in tokamaks and to resolve the disparity with respect to chirping observation in spherical and conventional tokamaks.